Approaches to Seasonality in Premodern Italy - Cossar, Roisin; Hewlett, Cecilia (Renaissance and Reformation / Renaissance et Réforme, 2021)
In this article, two historians of medieval and early modern Italy explore the impact of seasonal rhythms and routines on the social structures and practices of rural communities in central and northern Italy between the fourteenth and seventeenth centuries. We also investigate how rural inhabitants and those with authority over them responded to the challenges and opportunities posed by seasonal change. Primary sources include episcopal visitations, the diary of a rural priest, statutes from rural communities, testimony before episcopal courts, chronicles, and the records of magistracies in mountain communities. Studying the relationship between seasonality, sociability, and power relations in rural communities challenges one-dimensional narratives of premodern “peasant” life and instead demonstrates the complex and fluid nature of rural society.